Assessing the Role of a Children's Collection in an Academic Library: A Case Study of Collaborative Collection Management. Issue 3 (8th February 2021) - Wegmann, Mary; LaDuke, Aja; Lear, Marjorie; Henry Casesa, Rhianna
Abstract: The Sonoma State University Library's children's book collection is under-utilized by students in the School of Education, the primary intended audience, which prompted the Library to assess the role of this collection in the University setting. In an effort to learn more about the information-seeking needs and practices of students in the School of Education, the Education Liaison Librarian and Collection Development Librarian collaborated with faculty in the Department of Literacy Studies and Elementary Education to observe text set presentations from students in five classes and design a student-driven assessment of the children's collection. Following the student assessment, the librarians compared the criteria students used to select and deselect books with the criteria the librarians use to develop and weed the collection; the librarians used this information to refine collection management, organization, and wayfinding strategies for the collection so it aligns more closely with the students' needs. This article describes the collaboration and results of the student assessment from the perspectives of both the librarians and the School of Education faculty.